QUALITY OF THE GROUNDWATER IN ŠIAULIAI CITY - Karosienė, Sigita (PROFESSIONAL STUDIES: Theory And Practice, 2022)
In Lithuania, only underwater is used for drinking; its resources are large and the quality of this water is higher than that of the surface-water. Moreover, it is better protected from pollution. Implementation of water monitoring is a major state regulated control means to prevent from pollution. The article deals with the analysis of problems of the groundwater quality in Šiauliai city, the assessment of the monitoring results for the underwater in Šiauliai city referring to the investigation of the groundwater. Key words: underwater, groundwater, monitoring, quality of water.